Dual Polarization DQPSK ROF System with Duo Binary Precoding and Hybrid Amplification for Effective Hybrid SMF FSO Transmission Medium (ELEKTRIKA- Journal of Electrical Engineering, 2023)
This article demonstrates the utilization of a hybrid amplification technique on the transmission part of the proposed hybrid medium transmission system which includes both using Single Mode Fiber (SMF) with 60 km and Free Space Optic (FSO) with a range between 5 km and 25 km. It has included four weather situations with an investigation of the FSO medium-based system performance. The system uses 64 channels based on Dual Polarization-Differential Quadratic Phase Shift Keying (DP-DQPSK) Dense Wavelength Division Multiplexing (DWDM) for the Radio over Fiber (RoF) system using the Duo Binary coding scheme to improve the system efficiency in general and the cross-talk in particular. The investigations will include using the hybrid amplifiers of Erbium Doped Fiber Amplifier (EDFA) and Optical Amplifier (OA) for transmission. The analysis results show that using the hybrid amplification could improve the transmission to reach 25 km for light air case, meanwhile, for light haze, it could reach up to 20 km. Moderate haze could improve transmission efficiency for a distance of 7 km. Finally, for moderate rain situations, the transmission could be further improved to cover a distance of up to 5 km.